2014
DOI: 10.1586/14787210.2015.981156
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-associated bacterial pneumonia; managing and controlling infection on two fronts

Abstract: Bacterial pneumonia complicating influenza is well-recognized as a severe manifestation of influenza, accounting for a substantial number of deaths from the 1918 influenza pandemic. Influenza-associated bacterial pneumonia remains a major contributor to the burden of influenza, and poses new challenges as antibiotic-resistant organisms such as methicillin-resistant Staphylococcus aureus spread. We provide an overview of the current state of knowledge of the epidemiology and co-pathogenesis of influenza-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 127 publications
0
16
0
7
Order By: Relevance
“…Community-acquired pneumonia (CAP) is the most common type of pneumonia, and the incidence of CAP requiring hospitalization is highest among the elderly [4]. Influenza-associated bacterial pneumonia (i.e., combined bacterial-viral, or secondary bacterial) is more prevalent during seasonal outbreaks and pandemics than primary viral pneumonia [6,7]. The elderly are vulnerable to influenzaassociated pneumonias and it is recognized that CAP may result from viral coinfections like influenza [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Community-acquired pneumonia (CAP) is the most common type of pneumonia, and the incidence of CAP requiring hospitalization is highest among the elderly [4]. Influenza-associated bacterial pneumonia (i.e., combined bacterial-viral, or secondary bacterial) is more prevalent during seasonal outbreaks and pandemics than primary viral pneumonia [6,7]. The elderly are vulnerable to influenzaassociated pneumonias and it is recognized that CAP may result from viral coinfections like influenza [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumococcal pneumonias including CAP begin with asymptomatic nasopharynx colonization [6,8,9]. Recently, an eloquent series of studies in a murine model of coinfection demonstrated how influenza promotes pneumococcal proliferation during colonization [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations